Changes in Patient Safety Culture in Palestinian Public Hospitals: Impact of Quality and Patient Safety Initiatives and Programs. Issue 3 (September 2018) - Hamdan, Motasem; Saleem, Abed Alra'oof
Abstract : Objectives: To assess the changes in the patient safety culture between 2011 and 2016 after the implementation of patient safety initiative in Palestinian public hospitals. Methods: A cross-sectional quantitative design employed using the Hospital Survey on Patient Safety Culture to collect data. Participants were 1, 229 clinical and nonclinical employees from all public hospitals in the West Bank. Results: Significant improvements were observed in patient safety culture with positive responses to 10 (83.3%) composite categories and 36 (86.0%) items of the Hospital Survey on Patient Safety Culture since the baseline survey in 2011 ( P < 0.05). The increase in the percent of positive responses to the survey composites ranged from 9.1% ( P < 0.001) to "Frequency of events reported" to 3.8% for "Teamwork across hospital units" ( P < 0.001). Significant decrease in positive responses to "Staffing" (11.4%) was observed ( P < 0.05); no significant change was observed in "Organizational learning—continuous improvement" ( P > 0.05). Most participants (70.5%) rated patient safety level in their units/hospital as 'Excellent/Very good', with an increase of 6.3% from the baseline ( P < 0.001); no significant increase in the number of reported events in the past 12 months was observed ( P < 0.05). Conclusions: Compared with the baseline survey results, patients' safety initiatives and quality improvement programs had positive effect on the safety culture in public Palestinian hospitals.